Digital marketing assistance for MSMEs products in Kutai Kartanegara Regency - Surahman Surahman; Ahyar Muhammad Diah; Hendrik Batoteng; Rif’ah Rif’ah; Amelia Dwisafira; Sarlivia Sarlivia; Riza Meidinata (Community Empowerment, 2023)
The community service program aims to provide an understanding of current technological developments, especially marketing digitalization. Training and mentoring were attended by MSME actors in the Loa Kulu District area. The program carried out are: 1) providing information related to digital marketing; 2) socialization of the establishment of MSME clinics; 3) training and assistance in using websites and social media; and 4) product shooting techniques. The results of the program show that MSME actors already have knowledge about the use of technology for marketing their products. Especially with the facilitation from the local government, the role of MSMEs in supporting regional economic growth is expected to be well realized.